Grazing snaplage residue as a roughage source for finishing beef cattle: effects on beef production, soil property, and subsequent crop yield - Lima, Ítalo Braz Gonçalves de (2022)
Integrated crop-livestock system (ICLS) is a management practice that uses the same land area to produce one crop, followed by livestock production, and usually followed by similar crops or not. This system aims to take advantage of the direct and indirect benefits brought by each component to the other in a complementary mutualistic relationship. The main objective of producing a corn crop is to harvest grain (for human or animal food) or to produce silage (exclusively for animal feed). Silage is a process of food conservation through anaerobic fermentation, and there are several types of silage. The choice of the most appropriate type of silage can vary with the objective of the farm, the location, and the time of the year. Snaplage is silage produced using only the corn ear (cob, husk, and grains). However, this process leaves a large quantity of residue consisting of leaf and stem behind, which remains in the area as a ground cover. A different strategy for using this residue would be grazing by animals. However, there are still concerns among producers and researchers if animal grazing would affect the soil positively or negatively, and consequently, the subsequent crop yield. Another question to be evaluated is whether an increase in stocking rate could compromise the performance of the animals. The experimental area was divided into paddocks with high stocking rates (more animals per unit of area), low stocking rates (fewer animals per unit of area), and ungrazed paddocks (no animals). This research demonstrated that the amount of residue decreased over time in all the paddocks, especially the more digestible material such as leaf and sheath. When planting the next crop, the grazed paddocks had less residue than the ungrazed ones. The disappearance is a result of grazing and trampling by the animals and weathering. Grazing by the animals did not compact the soil, one of the indicators of physical characteristics, at either of the stocking rates evaluated. Grazing by animals increased the amount of soil nutrients, nitrogen, phosphorus, and potassium. In both stocking rates, the animals consumed similar amount of residue and feed daily and consequently had similar performance. However, at the higher stocking rate, production per unit of area was double compared to the lower stocking rate. The subsequent crop yield increased when the paddocks were grazed compared to ungrazed ones. Thus, we concluded that it is possible to use the residue for animal finishing in an ICLS, adding cattle production between two crop rotations without affecting the soil’s physical characteristics and the animal’s performance. Putting more animals in the area allows for doubling the productivity per unit area, and adding animals positively affects the subsequent crop yield.